2005
DOI: 10.1139/t05-034
|View full text |Cite
|
Sign up to set email alerts
|

Application of geophysical methods for the investigation of the large gravitational mass movement of Séchilienne, France

Abstract: International audienceSeveral geophysical techniques (electromagnetic profiling, electrical tomography, seismic refraction tomography, and spontaneous potential and seismic noise measurement) were applied in the investigation of the large gravitational mass movement of Séchilienne. France. The aim of this study was to test the ability of these methods to characterize and delineate the rock mass affected by this complex movement in mica schists, whose lateral and vertical limits are still uncertain. A major obs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(65 citation statements)
references
References 26 publications
2
60
0
3
Order By: Relevance
“…The landslide shows a higher hydraulic conductivity than the underlying stable bedrock (Vengeon, 1998;Meric et al, 2005;Le Roux et al, 2011), thus leading to a landslide perched aquifer (Guglielmi et al, 2002). The recharge of the landslide perched aquifer is essentially local, enhanced by the trenches and the counterscarps which tend to limit the runoff and to facilitate groundwater infiltration in the landslide area.…”
Section: Geological Settings and Rainfall Triggeringmentioning
confidence: 99%
“…The landslide shows a higher hydraulic conductivity than the underlying stable bedrock (Vengeon, 1998;Meric et al, 2005;Le Roux et al, 2011), thus leading to a landslide perched aquifer (Guglielmi et al, 2002). The recharge of the landslide perched aquifer is essentially local, enhanced by the trenches and the counterscarps which tend to limit the runoff and to facilitate groundwater infiltration in the landslide area.…”
Section: Geological Settings and Rainfall Triggeringmentioning
confidence: 99%
“…Comparisons in other well known cases of deep seated landslides such as the Séchilienne landslide (Meric et al, 2005) or the Rosone slope (Binet et al, 2007) should also be conducted in order to validate the methodology at this scale.…”
Section: Resultsmentioning
confidence: 99%
“…This method has been widely used to model the landslides [e.g. [6][7][8]. It is observed that lateral velocity changes can be imaged competently by the use of the seismic tomography method [9] and [10] the utilized seismic tomography.…”
Section: Introductionmentioning
confidence: 99%